Marketing Communication Strategies for The Sale of BOYNEXTDOOR Merchandise by Tousdoor’s Go on The LINE App - Ayu Apriliyani; Siti Khumayah; Welly Wihayati (Green Publisher Indonesia, 2026)
This study aimed to determine the marketing communication strategies implemented by Tousdoor’s Go to increase sales of BOYNEXTDOOR merchandise through the LINE app and to identify the supporting and inhibiting factors. This study employed a descriptive qualitative approach. Data were collected through in-depth interviews with Tousdoor’s Go managers and members who had previously purchased BOYNEXTDOOR merchandise. The results indicated that Tousdoor’s Go optimized direct marketing through private and group messages, responsive personal selling, visual advertising in LINE Notes, voluntary word of mouth through testimonials, and interactive marketing through polls and reactions. Supporting factors included proof of authenticity, friendly interactions, and LINE features that fostered community engagement. Inhibiting factors included delayed responses when offline, limited sales promotions, and the absence of major events and influencer collaborations. This study concluded that Tousdoor’s Go’s marketing communication strategy was effective in increasing the trust and engagement of fans (ONEDOOR), although the results could be further optimized through channel integration and promotional strategies.